2022
DOI: 10.3389/fonc.2022.1005812
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of RNA cargo of extracellular vesicles in breast cancer patients undergoing neoadjuvant chemotherapy

Abstract: Extracellular vesicles (EVs) are g7aining increased attention as carriers of cancer-derived molecules for liquid biopsies. Here, we studied the dynamics of EV levels in the plasma of breast cancer (BC) patients undergoing neoadjuvant chemotherapy (NAC) and explored the relevance of their RNA cargo for the prediction of patients’ response to the therapy. EVs were isolated from serial blood samples collected at the time of diagnosis, at the end of NAC, and 7 days, 6, and 12 months after the surgery from 32 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The identification of differentially expressed small RNAs holds considerable diagnostic potential, particularly in cancer and cardiovascular diseases [ 6 , 7 , 8 , 9 , 53 ]. A preliminary iteration of the presented program has been utilised in recent publications focusing on the analysis of extracellular vesicle contents, engaging in discussions about the biological interpretations of the results [ 51 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The identification of differentially expressed small RNAs holds considerable diagnostic potential, particularly in cancer and cardiovascular diseases [ 6 , 7 , 8 , 9 , 53 ]. A preliminary iteration of the presented program has been utilised in recent publications focusing on the analysis of extracellular vesicle contents, engaging in discussions about the biological interpretations of the results [ 51 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, nine studies (60%) [ 26 , 28 , 55 , 56 , 58 , 59 , 60 , 62 , 63 ] received a “low ROB”, four studies (27%) [ 57 , 61 , 65 , 66 ] were assigned an “unclear ROB” rating, and two studies (13%) [ 54 , 64 ] were assigned a “high ROB”. The omission of appropriate statistical analysis for predicting model validation and information in the first three domains (i.e., participants, predictors, and outcome) was a frequent source of bias in terms of high and unclear judgment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, including our recent study of breast cancer, have shown that EV concentrations in body fluids are increased in cancer patients as compared to healthy controls and their levels reflect clinical events such as chemotherapy or surgery, thus suggesting that the excess EVs are produced in the body due to the disease process or treatment ( Lázaro-Ibáñez et al, 2014 ; Cappello et al, 2017 ; Krafft et al, 2017 ; Menck et al, 2017 ; König et al, 2018 ; Sadovska et al, 2022 ). Therefore, we expected that the EV numbers should decrease after the surgical removal of the tumor.…”
Section: Discussionmentioning
confidence: 99%